Digital transformation: The role of AI, social dynamics, and political support on the quality of strategic decisions and their implications for the progress of Islamic banking in Malaysia and Indonesia - Ahmad Dahlan; Muhammad Hakimi Mohd Shafia; Tatung Tatung; Basrowi Basrowi (International Journal of Data and Network Science)
The research design uses a quantitative approach, especially correlational, verification or hypothesis testing based on empirical data in the field. The population of this research is all Islamic banking customers, totaling around 33,600,000 people. The sample size for this study was 178 people, which was determined using the Joseph F. Hair formula. The research sample was selected randomly using stratified random sampling techniques to represent the relevant population. Data was collected using a questionnaire which was distributed to selected samples using a Google form. Primary data was analyzed using SMART PLS. The results indicate that the role of AI has an impact on the Quality of Strategic Decisions; Social Dynamics have an impact on the Quality of Strategic Decisions; Political Support has an impact on the Quality of Strategic Decisions; The role of AI has an impact on the Progress of Islamic Banking, Social Dynamics has an impact on the Progress of Islamic Banking; Political Support has an impact on the Progress of Islamic Banking; The quality of strategic decisions has an impact on the progress of Islamic banking; Quality of Strategic Decisions mediates the relationship between the Role of AI and the Progress of Islamic Banking; Quality of Strategic Decisions mediates the relationship between Social Dynamics and Islamic Banking Progress; and finally, Quality of Strategic Decisions mediates the relationship between Political Support and Islamic Banking Progress.